2017
DOI: 10.5194/amt-2017-397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homogenizing and Estimating the Uncertainty in NOAA’s Long Term Vertical Ozone Profile Records Measured with the Electrochemical Concentration Cell Ozonesonde

Abstract: Abstract. NOAA's program of long term monitoring of the vertical distribution of ozone with Electrochemical ConcentrationCell (ECC) ozonesondes has undergone a number of changes over the 50 year record. In order to produce a homogenous data set, these changes must be documented and where necessary, appropriate corrections applied. This is the first comprehensive and consistent reprocessing of NOAA's ozonesonde data records that corrects for these changes using the rawest form of the 15 data (cell current and p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…Uncertainties in the background/current term (red) are highest around the tropopause region where ozone measurements are a minimum (gray line) and I B approaches I M , meaning the total uncertainty approaches the measured signal. This is similar to the results in Witte et al () that reported on ozone uncertainties in the reprocessed tropical Southern Hemisphere Additional Ozonesondes data set and Sterling et al () that presented uncertainty estimates for profiles at eight NOAA ozonesonde stations.…”
Section: Uncertainties In the Wff Reprocessed Ozone Recordssupporting
confidence: 91%
See 3 more Smart Citations
“…Uncertainties in the background/current term (red) are highest around the tropopause region where ozone measurements are a minimum (gray line) and I B approaches I M , meaning the total uncertainty approaches the measured signal. This is similar to the results in Witte et al () that reported on ozone uncertainties in the reprocessed tropical Southern Hemisphere Additional Ozonesondes data set and Sterling et al () that presented uncertainty estimates for profiles at eight NOAA ozonesonde stations.…”
Section: Uncertainties In the Wff Reprocessed Ozone Recordssupporting
confidence: 91%
“…Over time, refinements in operating procedure protocols, changes in the ECC instrument, and adjustments in the sensing solution have created inhomogeneities in the long‐term station data records (van Malderen et al, ; Sterling et al, ; Tarasick et al, ; Witte et al, ). We apply well‐established guidelines from Smit12 for reprocessing and homogenizing the July 1995 to July 2018 WFF ozonesonde records.…”
Section: Wff Reprocessing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Malderen et al () also applied Smit12 uncertainties to the ECC ozonesonde measurements at Uccle (Belgium). Sterling et al () applied the formula to two SHADOZ stations (Hilo, Hawaii, and Pago Pago, American Samoa), Boulder, CO, and the South Pole, and Tarasick et al () applied their own uncertainty estimates to the Canadian ozonesonde records, taking into account the uncertainty terms in equation . We take advantage of theses studies to compare with our methods and results.…”
Section: The Ozone Uncertainty Equationmentioning
confidence: 99%